Saúde emocional de alunos e professores do alto sertão sergipano durante o retorno às atividades presenciais em meio a pandemia da Covid-19 - Santos, Eliziane Vitória (2023)
After the appearance of COVID-19 cases in Wuhan, China, the World Health Organization (WHO) understood that COVID-19 is a global emergency disease. Because it is a pathology with a high level of contamination, the WHO has recommended the practice of social isolation, the use of masks, and hand hygiene as essential measures to avoid contamination by SARSCoV-2. Front to the need to avoid crowds, presential activities at schools were interrupted, students and teachers began to meet only in virtual environments, but access to technological resources is not a reality for all Brazilian students, which caused gaps in learning through the difficulty of students accessing online classes. In addition, emotional damage is already observed among teachers and students, as social isolation caused drastic changes in daily life, which favored the development of symptoms of anxiety and depression. In this sense, this study tried to understand the emotional damage caused by social isolation to teachers and high school students in the high hinterlands of Sergipe, because understanding how the emotional health of students and teachers is found is important so that school management can plan in an appropriate way for the return of presential classes, in order to try to repair the gaps in student learning caused by the COVID-19 pandemic. The study is characterized as a quantitative research with a descriptive approach, for its development a questionnaire was applied to 118 high school students of the night and full-time shifts of 28 de Janeiro Excellence Center, with questions related to the period of online classes, preparation for ENEM and other entrance exams, access to technological resources during online classes and return to presential classes, as well as the Beck-BAI Anxiety Inventory and the Beck-BDI Depression Inventory. Nine high school teachers also participated in the study, who answered a questionnaire related to online classes, the feeling of security in returning to presential classes, the Beck-BAI Anxiety Inventory and the Beck-BDI Depression Inventory. Based on descriptive statistics and one-way statistical tests (ANOVA), t-Test and Principal Component Analysis (PCA), the following results were obtained: in addition to damage to learning, according to the Beck inventories between night and full-time shifts full-time students have a higher degree of anxiety, (t(116) = 4.464 and p < 0.001) and also depressed behavior (t(116) = 4.382 and p < 0.001), when observed between full-time classes, there is no difference statistics regarding to anxiety in the same way the night students, in posttest analysis it was observed that the 1st and 2nd full grades are more anxious than the students of the 1st and 2nd night grades, but there was no statistical difference between the participants of the 3rd night grade and integral for anxiety. Furthermore, between the sexes, women are more anxious and depressed than men. As for the teachers, 89% of the participants present a minimum degree of anxiety and 100% a minimum degree of depression. Through the results, it is concluded that there is a need to create emotional health care strategies in the school environment, therefore, it is necessary that law nº 13.935, of December 2019, be fulfilled, and psychology and social assistance professionals start to contribute to planning activities with teachers and school management, with regard to emotional health during the return to presential classes.